Phase change heat storage wood-plastic composite material and preparation method thereof

By using a composite structure of intermediate and overlay layers and a specific extrusion process, the thermal stability, durability, and mechanical properties of TES-WPC have been addressed, enabling high-performance and large-scale production of the material.

CN119261330APending Publication Date: 2025-01-07ANHUI GUOFENG WOOD PLASTIC COMPOSITE
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411370551.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing phase change thermal storage wood-plastic composites (TES-WPC) have poor thermal stability, poor durability, and decreased mechanical properties, especially the interfacial bonding failure caused by paraffin agglomeration and volume expansion.

Method used

The composite structure of the intermediate layer and the coating layer is adopted. The intermediate layer is composed of wood fiber powder, phase change material, porous material powder and grafted polyethylene, and the coating layer is composed of high-density polyethylene and grafted polyethylene. It is prepared by a specific extrusion process and uses siloxane to improve the interfacial bonding.

Benefits of technology

It improves the thermal stability, durability and mechanical properties of phase change heat storage wood-plastic composites, and the preparation method is simple and easy to scale up.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005067462680000071
    Figure BDA0005067462680000071
  • Figure BDA0005067462680000081
    Figure BDA0005067462680000081
  • Figure BDA0005067462680000082
    Figure BDA0005067462680000082
Patent Text Reader

Abstract

The invention discloses a phase-change heat-storage wood-plastic composite material and a preparation method thereof. The phase-change heat-storage wood-plastic composite material comprises a middle layer and a coating layer coating the middle layer, the middle layer comprises the following raw materials in parts by weight: 45-60 parts of wood fiber powder, 20-25 parts of high-density polyethylene, 10-15 parts of a phase change material, 5-10 parts of porous material powder, 2.5-3 parts of maleic anhydride grafted polyethylene and 0.3-0.5 part of siloxane; the coating layer is prepared from the following raw materials in parts by weight: 10 parts of high-density polyethylene, 0.2 to 0.3 part of maleic anhydride grafted polyethylene and 0.1 to 0.3 part of pigment color masterbatch. The prepared phase change heat storage wood-plastic composite material has good thermal stability, durability and mechanical property, and the preparation method is simple, easy to implement and convenient for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wood-plastic composite materials, and in particular to a phase-change heat-storage wood-plastic composite material and a preparation method thereof. Background Art

[0002] Phase change material (PCM) refers to a material that can store, convert and utilize heat when it changes phase. Since heat is absorbed and released during the phase change process, PCM can present a temperature interval that is approximately constant within a certain range. This temperature is the phase change temperature, and the heat absorbed or released is the phase change latent heat of PCM. Phase change materials have been widely used in the energy field, such as construction, aerospace, electric power industry, solar energy, agriculture, storage and transportation of food and medicine, and utilization of waste energy.

[0003] Phase change thermal storage wood-plastic composite (TES-WPC) is a type of material prepared by mixing polymer materials, wood materials and phase change materials. It has the characteristics of wood-plastic materials and phase change materials and has been widely used in fields such as building energy conservation.

[0004] TES-WPC has obvious temperature regulation ability, and as the mass fraction of paraffin in TES-WPC increases, the heat storage capacity of TES-WPC becomes stronger. However, thermogravimetric analysis and hot and cold cycle experiments show that TES-WPC has poor thermal stability and durability. After the cycle experiment, the melting enthalpy value decreased by about 37%. In addition, since paraffin mainly aggregates around wood powder, it forms a barrier to the combination of wood powder and HDPE. At the same time, paraffin becomes liquid during the phase change process, and the volume expands, which further aggravates the destruction of the interface bonding of TES-WPC and leads to a decrease in mechanical properties. Summary of the invention

[0005] The main purpose of the present invention is to provide a phase change thermal storage wood plastic composite material and a preparation method thereof, aiming to solve the technical problems of poor thermal stability, poor durability and decreased mechanical properties of the existing TES-WPC.

[0006] To achieve the above object, the present invention provides a phase change heat storage wood-plastic composite material, comprising an intermediate layer and a coating layer coated outside the intermediate layer;

[0007] In parts by weight, the middle layer comprises the following raw materials: 45-60 parts of wood fiber powder, 20-25 parts of high-density polyethylene, 10-15 parts of phase change material, 5-10 parts of porous material powder, 2.5-3 parts of maleic anhydride grafted polyethylene, and 0.3-0.5 parts of siloxane;

[0008] In parts by weight, the coating layer comprises the following raw materials: 10 high-density polyethylene, 0.2-0.3 maleic anhydride grafted polyethylene, and 0.1-0.3 pigment masterbatch.

[0009] Furthermore, the mass ratio of the intermediate layer to the coating layer is 94-95:5-6.

[0010] Furthermore, the particle size of the wood fiber powder is 80-120 meshes, and the wood fiber is one of corn straw, wheat straw, rice straw, and wood, or a mixture of two or more of them in any proportion.

[0011] Furthermore, the phase change material is paraffin.

[0012] Furthermore, the particle size of the porous material powder is 10-50 μm, and the porous material is one of graphite oxide, graphene oxide, diatomaceous earth, expanded perlite, and vermiculite, or a mixture of two or more thereof in any proportion.

[0013] Furthermore, the siloxane is polydimethylsiloxane.

[0014] The present invention also provides a method for preparing the phase-change heat storage wood-plastic composite material, comprising the following steps:

[0015] (1) adding siloxane to wood fiber powder and stirring evenly to obtain treated wood fiber powder;

[0016] (2) Drying the porous material powder, then adding the phase change material to the porous material powder under a vacuum condition of -0.03 to 0.05 MPa, introducing nitrogen gas to pressurize the mixture to 3 to 4 MPa, and then taking out the mixture of the porous material powder and the phase change material for drying to obtain the treated phase change material;

[0017] (3) The treated wood fiber powder, the treated phase change material and the remaining raw material of the middle layer are mixed evenly and then put into a first single screw extruder for melt extrusion at a barrel temperature of 160 to 190° C.;

[0018] The raw materials of the coating layer are mixed evenly and then put into the second single-screw extruder for melt extrusion at a barrel temperature of 130-175°C;

[0019] The melt extruded by the first single screw extruder and the second single screw extruder is passed into a co-extrusion die with a die temperature of 180-250° C. and cooled to 120-170° C. by cooling water or compressed air at the die mouth to obtain the phase change thermal storage wood plastic composite material.

[0020] Furthermore, in step (2), the porous material powder is graphene oxide, the drying treatment temperature is 103-105° C., the time is 24 hours, and the baking treatment temperature is 40° C., and the time is 2 hours.

[0021] The beneficial effects of the present invention are embodied in:

[0022] The phase-change heat-storage wood-plastic composite material prepared by the invention has good thermal stability, durability and mechanical properties, and the preparation method is simple, easy to implement and convenient for large-scale production. DETAILED DESCRIPTION

[0023] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0024] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods; unless otherwise specified, the methods used in the examples of the present invention are methods known to those skilled in the art. Among them: the wood fiber powder is poplar wood powder with a diameter of 80 to 120 meshes.

[0025] Example 1

[0026] Preparation of phase change thermal storage wood-plastic composites

[0027] The raw material composition of the middle layer is as follows: by weight, 52 parts of wood fiber powder, 23 parts of high-density polyethylene, 13 parts of paraffin wax, 8 parts of graphene oxide powder with a particle size of 10 to 50 μm, 2.8 parts of maleic anhydride grafted polyethylene, and 0.4 parts of polydimethylsiloxane;

[0028] The raw material composition of the coating layer is as follows: by weight, high-density polyethylene 10, maleic anhydride grafted polyethylene 0.25, pigment masterbatch 0.2;

[0029] The mass ratio of the intermediate layer to the coating layer is 94:6.

[0030] The preparation method comprises the following steps:

[0031] (1) adding polydimethylsiloxane to wood fiber powder and stirring evenly to obtain treated wood fiber powder;

[0032] (2) placing the graphene oxide powder in an electric blast drying oven and drying it at 104°C for 24 hours, then adding paraffin wax to the graphene oxide powder under a vacuum condition of 0.01MPa, and then introducing nitrogen gas to pressurize it to 3.5MPa, then taking out the mixture of graphene oxide powder and paraffin wax and placing it in a 40°C oven for heating for 2 hours, taking it out and stirring it for 5 minutes every half an hour, to obtain a treated phase change material;

[0033] (3) mixing the treated wood fiber powder, the treated phase change material and the remaining raw material of the middle layer uniformly and then feeding them into a first single screw extruder for melt extrusion at a barrel temperature of 175° C.;

[0034] The raw materials of the coating layer are mixed evenly and then put into the second single-screw extruder for melt extrusion at a barrel temperature of 155°C;

[0035] The melt extruded by the first single-screw extruder and the second single-screw extruder is passed into a co-extrusion die with a die temperature of 210° C. and cooled to 150° C. by cooling water or compressed air at the die mouth to obtain the phase-change heat storage wood-plastic composite material.

[0036] Example 2

[0037] Preparation of phase change thermal storage wood-plastic composites

[0038] The raw material composition of the middle layer is as follows: by weight, 45 parts of wood fiber powder, 20 parts of high-density polyethylene, 10 parts of paraffin wax, 5 parts of graphene oxide powder with a particle size of 10 to 50 μm, 2.5 parts of maleic anhydride grafted polyethylene, and 0.3 parts of polydimethylsiloxane;

[0039] The raw material composition of the coating layer is as follows: by weight, high-density polyethylene 10, maleic anhydride grafted polyethylene 0.2, pigment masterbatch 0.1;

[0040] The mass ratio of the intermediate layer to the coating layer is 95:5.

[0041] The preparation method comprises the following steps:

[0042] (1) adding polydimethylsiloxane to wood fiber powder and stirring evenly to obtain treated wood fiber powder;

[0043] (2) placing the graphene oxide powder in an electric blast drying oven and drying it at 103°C for 24 hours, then adding paraffin wax to the graphene oxide powder under a vacuum condition of -0.03 MPa, and then introducing nitrogen gas to pressurize it to 3 MPa, then taking out the mixture of graphene oxide powder and paraffin wax and placing it in a 40°C oven for heating for 2 hours, taking it out and stirring it for 5 minutes every half an hour, to obtain a treated phase change material;

[0044] (3) mixing the treated wood fiber powder, the treated phase change material and the remaining raw material of the middle layer uniformly and then feeding them into a first single screw extruder for melt extrusion at a barrel temperature of 160° C.;

[0045] The raw materials of the coating layer are mixed evenly and then put into the second single-screw extruder for melt extrusion at a barrel temperature of 130°C;

[0046] The melt extruded by the first single-screw extruder and the second single-screw extruder is passed into a co-extrusion die with a die temperature of 180° C. and cooled to 120° C. by cooling water or compressed air at the die mouth to obtain the phase-change heat storage wood-plastic composite material.

[0047] Example 3

[0048] Preparation of phase change thermal storage wood-plastic composites

[0049] The raw material composition of the middle layer is as follows: by weight, 60 parts of wood fiber powder, 25 parts of high-density polyethylene, 15 parts of paraffin wax, 10 parts of graphene oxide powder with a particle size of 10 to 50 μm, 3 parts of maleic anhydride grafted polyethylene, and 0.5 parts of polydimethylsiloxane;

[0050] The raw material composition of the coating layer is as follows: by weight, high-density polyethylene 10, maleic anhydride grafted polyethylene 0.3, pigment masterbatch 0.3;

[0051] The mass ratio of the intermediate layer to the coating layer is 94.5:5.5.

[0052] The preparation method comprises the following steps:

[0053] (1) adding polydimethylsiloxane to wood fiber powder and stirring evenly to obtain treated wood fiber powder;

[0054] (2) placing the graphene oxide powder in an electric blast drying oven and drying it at 105° C. for 24 h, then adding paraffin wax to the graphene oxide powder under a vacuum condition of 0.05 MPa, and then introducing nitrogen gas to pressurize it to 4 MPa, and then taking out the mixture of graphene oxide powder and paraffin wax and placing it in a 40° C. oven for heating for 2 h, taking it out and stirring it for 5 min every half an hour to obtain a treated phase change material;

[0055] (3) mixing the treated wood fiber powder, the treated phase change material and the remaining raw material of the middle layer uniformly and then feeding them into a first single screw extruder for melt extrusion at a barrel temperature of 190° C.;

[0056] The raw materials of the coating layer are mixed evenly and then put into the second single-screw extruder for melt extrusion at a barrel temperature of 175°C;

[0057] The melt extruded by the first single-screw extruder and the second single-screw extruder is passed into a co-extrusion die with a die temperature of 250° C. and cooled to 170° C. by cooling water or compressed air at the die mouth to obtain the phase-change heat storage wood-plastic composite material.

[0058] Comparative Example 1

[0059] In this comparative example, a phase change thermal storage wood-plastic composite material is prepared in the same manner as in Example 1, except that the entire coating layer is omitted, and maleic anhydride grafted polyethylene and polydimethylsiloxane are omitted as the raw materials of the intermediate layer.

[0060] Comparative Example 2

[0061] In this comparative example, a phase change thermal storage wood-plastic composite material is prepared in the same manner as in Example 1, except that the entire coating layer is omitted.

[0062] Comparative Example 3

[0063] In this comparative example, a phase-change heat storage wood-plastic composite material was prepared in the same manner as in Example 1, except that polydimethylsiloxane was omitted from the raw material of the middle layer.

[0064] Comparative Example 4

[0065] In this comparative example, a phase change thermal storage wood-plastic composite material is prepared in the same manner as in Example 1, except that maleic anhydride grafted polyethylene is omitted from the raw materials of the intermediate layer and the coating layer.

[0066] Comparative Example 5

[0067] In this comparative example, a phase change thermal storage wood-plastic composite material is prepared according to the method of Example 1, except that the operation of "then adding paraffin wax to the graphene oxide powder under a vacuum condition of 0.01 MPa, and then introducing nitrogen gas to pressurize it to 3.5 MPa" is replaced by "adding paraffin wax to the graphene oxide powder under normal pressure".

[0068] Comparative Example 6

[0069] In this comparative example, a phase change thermal storage wood-plastic composite material was prepared in the same manner as in Example 1, except that the step of "taking out the mixture of graphene oxide powder and paraffin and heating it in an oven at 40° C. for 2 h, and taking it out and stirring it for 5 min every half an hour" was omitted.

[0070] Performance test of phase change thermal storage wood plastic composites

[0071] 1. Infrared thermal image analysis (heat storage effect test)

[0072] The phase change thermal storage wood-plastic composite material samples (sample length×width×thickness of 400mm*210mm*140mm) prepared in the above embodiments and comparative examples were placed in a thermal environment of 150°, and the temperature of each sample was tested at different time periods using an infrared thermometer. Five samples were tested for each sample, and the average value was calculated. The results are shown in Table 1.

[0073] Table 1

[0074]

[0075] The lower the average surface temperature, the better the heat storage performance. This is because the paraffin inside can absorb part of the heat during the phase change process, thus slowing down the temperature change of TES-WPC.

[0076] 2. Durability test

[0077] The phase change thermal storage wood-plastic composite materials prepared in the above embodiments and comparative examples were subjected to 100 hot and cold cycles at -30°C-60°C, heating +20°C / 30min, and cooling -10°C / 30min. The melting and crystallization enthalpy values ​​of the materials at the beginning and after the hot and cold cycles were tested. The results are shown in Table 2 below.

[0078] Table 2

[0079]

[0080] 3. Mechanical properties test

[0081] The mechanical properties of the phase change thermal storage wood-plastic composite materials prepared in the above examples and comparative examples were tested, and the results are shown in Table 3 below.

[0082] Table 3

[0083]

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A phase change heat storage wood-plastic composite material, characterized in that: comprising an intermediate layer and a covering layer covering the intermediate layer; In parts by weight, the middle layer comprises the following raw materials: 45-60 parts of wood fiber powder, 20-25 parts of high-density polyethylene, 10-15 parts of phase change material, 5-10 parts of porous material powder, 2.5-3 parts of maleic anhydride grafted polyethylene, and 0.3-0.5 parts of siloxane; In parts by weight, the coating layer comprises the following raw materials: 10 high-density polyethylene, 0.2-0.3 maleic anhydride grafted polyethylene, and 0.1-0.3 pigment masterbatch.

2. The phase change thermal storage wood-plastic composite material according to claim 1, characterized in that: The mass ratio of the intermediate layer to the coating layer is 94-95:5-6.

3. The phase change thermal storage wood-plastic composite material according to claim 1 or 2, characterized in that: The particle size of the wood fiber powder is 80-120 meshes, and the wood fiber is one of corn straw, wheat straw, rice straw, and wood, or a mixture of two or more of them in any proportion.

4. The phase change thermal storage wood-plastic composite material according to claim 1 or 2, characterized in that: The phase change material is paraffin.

5. The phase change thermal storage wood-plastic composite material according to claim 1 or 2, characterized in that: The particle size of the porous material powder is 10-50 μm, and the porous material is one of graphite oxide, graphene oxide, diatomaceous earth, expanded perlite, and vermiculite, or a mixture of two or more of them in any proportion.

6. The phase change thermal storage wood-plastic composite material according to claim 1 or 2, characterized in that: The silicone is polydimethylsiloxane.

7. The method for preparing the phase change thermal storage wood-plastic composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) adding siloxane to wood fiber powder and stirring evenly to obtain treated wood fiber powder; (2) Drying the porous material powder, then adding the phase change material to the porous material powder under a vacuum condition of -0.03 to 0.05 MPa, introducing nitrogen gas to pressurize the mixture to 3 to 4 MPa, and then taking out the mixture of the porous material powder and the phase change material for drying to obtain the treated phase change material; (3) The treated wood fiber powder, the treated phase change material and the remaining raw material of the middle layer are mixed evenly and then put into a first single screw extruder for melt extrusion at a barrel temperature of 160 to 190° C.; The raw materials of the coating layer are mixed evenly and then put into the second single-screw extruder for melt extrusion at a barrel temperature of 130-175°C; The melt extruded by the first single screw extruder and the second single screw extruder is passed into a co-extrusion die with a die temperature of 180-250° C. and cooled to 120-170° C. by cooling water or compressed air at the die mouth to obtain the phase change thermal storage wood plastic composite material.

8. The method for preparing the phase change thermal storage wood-plastic composite material as claimed in claim 7, characterized in that: In step (2), the porous material powder is graphene oxide, the drying temperature is 103-105° C., the time is 24 hours, and the baking temperature is 40° C., the time is 2 hours.

Citation Information

Patent Citations

  • Co-extrusion wood-plastic composite with anti-static surface and manufacturing method thereof

    CN105602106A

  • High strength wood-plastic coated coextruded composite material and preparation method thereof

    CN105644074A

  • Phase-change heat-storage wood-plastic composite and preparation method thereof

    CN106589519A

  • Flame-retardant wood-plastic phase change composite material

    CN107129702A

  • Method for improving flame retardant performance of co-extruded core-surface structure wood-plastic composite

    CN110181790A